Stimulasi Pulsed Electromagnetic Field (PEMF) pada Osteogenesis Pergerakan Gigi Ortodonti - Hafiedz Maulana; Yuyun Yueniwati; Diana Lyrawati; Nur Permatasari; Mohamad Hidayat (Fakultas Kedokteran Gigi Universitas Jember, 2023)
The prevalence of malocclusion and the need for orthodontic treatment in Indonesia is relatively very high. Orthodontic treatment that transmits mechanical forces to the periodontal ligament and alveolar bone cells can stimulate the periodontal ligament and alveolar bone remodeling. While this time, orthodontic treatment requires a long time, resulting in several adverse effects and discomfort. For this reason, a method that can accelerate orthodontic treatment is needed which aims to increase stability after active orthodontic treatment, to reduce the potential for relapse, and to accelerate retention time. Pulsed Electromagnetic Field (PEMF) stimulation is one of the methods that have this goal. This aim to study the stimulation mechanism of PEMF on the osteogenesis process of orthodontic tooth movement. Alveolar bone remodeling played an essential role in orthodontic tooth movement, is an active and dynamic process. The dynamic process depends on a balance between resorption and bone formation (osteogenesis). PEMF stimulation is a nonsurgical method that can promote osteogenesis through activation of Wnt signaling. Several studies showed that this method could accelerate retention time and orthodontic treatment. PEMF stimulated osteogenesis through activation of Wnt signaling in orthodontic tooth movement.